The Effectiveness of the Cluster Umbrella Strategy in the Development of Critical Thinking among Fifth Preparatory Students in the History Course - Hassan, Suaad Salman (International Journal of Psychosocial Rehabilitation, 2020)
The education process in Iraq faces several difficulties in general and the teaching of history in particular, among which many teachers resort to colonizing teaching methods and methods that depend on students memorizing historical facts and information without understanding them or realizing the interconnectedness between them and this leads to making the student’s role passively dependent on listening and listening without participation The actors in the lesson, which makes the process of communication between them and the teacher somewhat difficult, and here it is necessary to use different types of methods and methods during teaching to ensure the participation of all learners in the lesson, and this is an emphasis on the positive role for them and what they should be in the process Education and Learning (Al-Rabei, 2014, 437-466)